Ultra-low supply CMOS operational amplifier - Lean, Jun Xian. (2009)
This project proposes the fully differential folded-cascode 2 stage operational amplifier, including common mode feedback. This requires accurate sizing of each transistor in order to optimize the limited low voltage supply. Native NMOS transistor and bulkdriven PMOS transistor were used in this design which is found suitable for Low-Supply Operational Amplifier. The simulation system is based upon Chartered Semiconductor 0.18-μm CMOS IC in Cadence software under Linux operating system.